The Development of Mobile Application Based Customer Service System in Bank Sampah Malang - Nur Hayatin; Bayu Mavindo; Eko Budi Cahyono (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2017)
Malang Waste Bank, or commonly called Bank Sampah Malang (BSM), is a legal entity of incorporated cooperatives built by the Malang municipal government serving as a container of waste management, especially dry waste. During this time, the customer service process conducted in BSM has been not optimal, especially its online service. Some services have been accessible online through website but the information is limited only to the list of prices and types of waste received by BSM. While other necessary information needed by the customers such as balance checking, garbage collection schedule checking, and information about the types of saving managed by BSM has not been covered by the existing online system yet. This research has built an online customer service system based on mobile applications and SMS gateways for BSM. The purpose of the system is to facilitate the customers of BSM to obtain information about the garbage bank, especially for customers having high mobility. Interviews and observation are used as the method of the analysis of the system requirements. Meanwhile, the applications such as MySQL database, Web service, PHP CodeIgniter, SMS Gateway and Android as a language programming are used to develop the system. This system integrates android applications with web based applications by using web service. This system is made so that customers get better service. Evaluation results show the system that has been built has been successfully tested.